2001
DOI: 10.1182/blood.v98.9.2736
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+CD25+ cells: a naturally occurring population of regulatory T cells

Abstract: Despite thymic deletion of cells with specificity for self-antigens, autoreactive T cells are readily detectable in the normal T-cell repertoire. In recent years, a population of CD4(+) T cells that constitutively express the interleukin-2 receptor-alpha chain, CD25, has been shown to play a pivotal role in the maintenance of self-tolerance in rodent models. This study investigated whether such a regulatory population exists in humans. A population of CD4(+)CD25(+) T cells, taken from the peripheral blood of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
305
2
13

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 537 publications
(356 citation statements)
references
References 38 publications
33
305
2
13
Order By: Relevance
“…This subset of cells has been found in human solid tumors, tumor ascites fluids and hematological malignancies [32][33][34], and their presence correlated in human ovarian cancer with a poor prognosis [32,33]. Indirect evidence suggests that Tregs are able to suppress tumor-specific immunity [34][35][36][37][38][39][40][41][42], but definitive evidence of the role of this T cell subset in the immunopathogenesis of human cancer is still lacking.…”
Section: Inflammatory Leukocytes In the Tumor Microenvironmentmentioning
confidence: 99%
“…This subset of cells has been found in human solid tumors, tumor ascites fluids and hematological malignancies [32][33][34], and their presence correlated in human ovarian cancer with a poor prognosis [32,33]. Indirect evidence suggests that Tregs are able to suppress tumor-specific immunity [34][35][36][37][38][39][40][41][42], but definitive evidence of the role of this T cell subset in the immunopathogenesis of human cancer is still lacking.…”
Section: Inflammatory Leukocytes In the Tumor Microenvironmentmentioning
confidence: 99%
“…The chemokines CCL17 and CCL22 attract CCR4-bearing cells, in particular Th2-type cells (19)(20)(21) and regulatory Tregs (22,23). Recent studies have revealed the participation of the CCL17 and CCL22 proteins in diseases such as atopic dermatitis (30) and lymphoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…Since CCL17 and CCL22 signal through CCR4, they can act as chemoattractants for Th2 CD4 + T-cell-mediated immunity (19)(20)(21). CCR4 is also expressed on Tregs, which play an important role in maintaining immune balance and have been detected in the peripheral blood of humans (22,23). Tregs are known to be a potent inhibitor of the antitumour immune response (32).…”
Section: Alleles) (N=512 Alleles) -----------------------------------mentioning
confidence: 99%
See 2 more Smart Citations